PENGEMBANGAN KREATIVITAS DALAM SENTRA PERSIAPAN DI TA-TK AL AZHAR SYIFA BUDI SOLO - Linawati - (BUANA GENDER : Jurnal Studi Gender dan Anak, 2022)
This paper describes the development of creativity in the preparation center for TA-TK Al-Azhar Syifa Budi Solo. The preparation center is one of the learning centers in early childhood education institutions. This center is a place to play for reading, writing, math, and other activities that support children's preparation for primary school. However, it should be noted that provision for early childhood to continue primary school is not only reading and counting skills, but also children's creativity needs to be developed. The purpose of this study was to determine the role of the preparation center in developing children's creativity in Al Azhar Syifa Budi Solo Kindergarten. This research method uses descriptive qualitative research methods. The results of this study indicate that the four elements of creativity (person, process, press, product) are contained in learning at the center of creativity. The purpose of developing creativity in Al Azhar TA-Kindergarten is to build children's character and to recognize children's talents and interests. The teacher is the main key to developing children's creativity. Because the teacher plays a role in designing activities, selecting games, presenting games, and evaluating the results of children's play. There are efforts to improve teacher competence, namely by participating in seminars, workshops, training and competitions which are participated in by teachers.